Determination of Folic Acid in Syrian Cereals by High Performance Liquid Chromatography with UV-DAD Detection After SPE Extraction - Antakli, Saad; Sarkis, Nazera; Nabo, Nayla (Asian Journal of Chemistry, 2010)
Folic acid is a water soluble vitamin which has been determined in some Syrian cereals such as (flour, rice, semolina, corn, gram, borghol, lentil, triticum durm, triticum aestivum, lima bean) by HPLC-DAD detection after solid phase extraction clean up. For analytical conditions, we studied the folic acid determination by C8 and ODS columns. Isocratic system was used for C8 column. The mobile phase was with a volumetric mixture of 92 % A and 8 % B. The second one for ODS column, the separation was in a gradient system. The flow rate for both columns were 1 mL/min, the wavelength was 280 nm. The concentrations of folic acid varied from 0.02-1.90 μg/g.